Dexamethasone encapsulated PLGA nanoparticles for the treatment of neuroinflammation. Issue 2 (20th September 2022) - Stephen, Bjorn John; Chokriwal, Ankit; Sharma, Madan Mohan; Jain, Devendra; Saxena, Juhi; Dhaliwal, Harshdeep; Sharma, Vikram; Mishra, Rajeev; Kaur, Ramandeep; Singh, Abhijeet
Abstract : Neuroinflammation is a condition that contributes significantly to the pathogenesis and progression of several neurodegenerative disorders. Targeting neuroinflammation is a novel therapeutic approach for the treatment of these disorders. Dexamethasone is a steroid-based anti-inflammatory drug with the potential to treat neuroinflammation. However, to maintain the efficacy of the drug, dexamethasone needs to be coupled with an effective drug delivery vehicle to be able to be transported across the central nervous system. Poly(lactic- co -glycolic acid) (PLGA) nanoparticles have been used as drug delivery vehicles for the transport of drugs into the central nervous system. This paper describes the preparation and encapsulation of dexamethasone-loaded PLGA nanoparticles by using the solvent evaporation method. The statistical experimental design approach was performed, wherein response surface methodology was carried out to optimize the parameters associated with the synthesis process. Further, the kinetic model and drug release profile were also determined. The drug encapsulated nanoparticles were validated for their effectiveness in vitro. Toxicity studies revealed the nanodrug to be non-cytotoxic, and the Griess assay highlighted its ability to lower neuroinflammation. Further, genetic studies revealed that the anti-inflammatory properties of the nanodrug were successful in modulating neuroinflammation.